PENINGKATAN KEMAMPUAN KOMUNIKASI MATEMATIS SISWA SMP MELALUI MODEL LEARNING CYCLE 7E BERBANTUAN QUIZIZZ - Saputra, Jusep; Rany Nur Amalia; Fisher, Dahlia (Mathematics Education Study Program, FKIP, Universitas Pasundan, 2024)
This study aims to determine whether the improvement in mathematical communication skills of students who get the Learning Cycle 7E model assisted by quizizz is higher than students who get conventional learning models. The method used in this research is a quasi-experiment with a nonequivalent control group design. This study involved two classes as experimental and control classes. Students in the experimental class received learning with the Learning Cycle 7E model assisted by quizizz while the control class received learning with a conventional learning model. This study involved 30 students of class VIII A and 30 students of class VIII C at Pasundan 6 Bandung Junior High School. The instruments used in this study were 5 questions of mathematical communication ability test descriptions. Data analysis technique with two-sample comparison test (t-test). The collected data were processed using IBM SPSS 23.0 software for windows. The results showed that the improvement in mathematical communication skills of students who obtained the Learning Cycle 7E learning model assisted by quizizz was higher than students who obtained the conventional learning model.